PECULIARITIES OF CLASSIFICATION OF FINANCIAL INVESTMENTS AND THEIR EVALUATION - Rashidov Abror Roʻzimurod oʻgʻli (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
In this thesis, specific features of categorization of financial investments and their evaluation are studied, and proposals are developed on them.